Application of artificial intelligence in travel, hospitality, and tourism: a systematic literature review - Sathana, V. (Sri Lanka Institute of Marketing, 2025)
This study explores the applications of artificial intelligence (AI) in the travel, hospitality, and tourism sectors. A systematic literature review was conducted to gather and analyse knowledge in this domain, utilising the SPAR-4-SLR protocol for the review process. The 5W+1H framework was employed to structure and report the findings. A comprehensive extraction and analysis procedure identified relevant insights using content analysis. The results highlight several potential AI applications in these sectors, including chatbots, the Internet of Things (IoT), predictive analytics, natural language processing, robotics and automation, image and video recognition, and virtual, augmented, and mixed reality technologies. The roles of a chatbot are real-time assistance, booking support, personalised recommendations, multilingual customer interaction, post-travel engagement, and customer experience. The role of IoT is in smart hotel rooms, smart airports, wearable technology, location-based beacons, wristbands in theme parks, smart cities, and customer experiences. Predictive analytics is used for demand forecasting, dynamic pricing, airline operations, revenue management, tailored travel packages, destination management, and data-driven decision-making. Robotics and automation are applied to enhance customer service, operational efficiency, streamlined operations, and attraction engagement. Virtual, Augmented, and mixed reality include exploring destinations, virtual walkthroughs, pre-trip experiences, real-time experiences, interactive tours, virtual concierge services, themed resorts, and entertainment destinations, enhancing personalisation and innovative engagement. This research provides valuable insights into the transformative role of AI in the business sector and the travel, hospitality, and tourism industries, offering guidance for enhancing efficiency, personalisation, and innovation. It also highlights the need for supportive policies and ethical frameworks to ensure responsible AI adoption, benefiting businesses, customers, and society.
Keywords: Artificial intelligence; Chatbot; Internet of things; Natural language processing; Travel, Hospitality; Tourism